The History of the Relationship Between Lithuanians and Jews in XIX Century. Social and Economic Aspects - Vareikis, Vygandas (Sociologija. Mintis ir veiksmas, 2000)
The aim of this article is to analyze the development of socio-economical relations between Jews and Lithuanians in the nineteenth century and discuss the influence of the Lithuanian national ideology for the evolution of these relations. The analysis is developed on a few levels: the situation of Jewish community in Lithuania, the development of anti-Judaism and modern anti-Semitism, Lithuania’s catholic’s church attitude towards Jews and the ideas of anti-Judaism in the works of interwar period authors.